CARP-1 functional mimetics are a novel class of small molecule inhibitors of malignant pleural mesothelioma cells. - Shazia Jamal; Vino T Cheriyan; Magesh Muthu; Sara Munie; Edi Levi; Abdelkader E Ashour; Harvey I Pass; Anil Wali; Mandip Singh; Arun K Rishi (PLoS ONE)
Malignant pleural mesothelioma (MPM) is an asbestos-related thoracic malignancy that is characterized by late metastases, and resistance to therapeutic modalities. The toxic side-effects of MPM therapies often limit their clinical effectiveness, thus necessitating development of new agents to effectively treat and manage this disease in clinic. CARP-1 functional mimetics (CFMs) are a novel class of compounds that inhibit growth of diverse cancer cell types. Here we investigated MPM cell growth suppression by the CFMs and the molecular mechanisms involved. CFM-1, -4, and -5 inhibited MPM cell growth, in vitro, in part by stimulating apoptosis. Apoptosis by CFM-4 involved activation of pro-apoptotic stress-activated protein kinases (SAPKs) p38 and JNK, elevated CARP-1 expression, cleavage of PARP1, and loss of the oncogene c-myc as well as mitotic cyclin B1. Treatments of MPM cells with CFM-4 resulted in depletion of NF-κB signaling inhibitor ABIN1 and Inhibitory κB (IκB)α and β, while increasing expression of pro-apoptotic death receptor (DR) 4 protein. CFM-4 enhanced expression of serine-phosphorylated podoplanin and cleavage of vimetin. CFMs also attenuated biological properties of the MPM cells by blocking their abilities to migrate, form colonies in suspension, and invade through the matrix-coated membranes. Both podoplanin and vimentin regulate processes of cell motility and invasion, and their expression often correlates with metastatic disease, and poor prognosis. The fact that phosphorylation of serines in the cytoplasmic domain of podoplanin interferes with processes of cellular motility, CFM-4-dependent elevated phosphorylated podoplanin and cleavage of vimentin underscore a metastasis inhibitory property of these compounds, and suggest that CFMs and/or their future analogs have potential as anti-MPM agents.